Insights into the Interfacial Lewis Acid–Base Pairs in CeO2‐Loaded CoS2 Electrocatalysts for Alkaline Hydrogen Evolution. Issue 39 (18th August 2021) - Li, Jiayuan; Xia, Zhaoming; Xue, Qingyu; Zhang, Mingkai; Zhang, Sai; Xiao, Hai; Ma, Yuanyuan; Qu, Yongquan
Abstract: Despite the known efficacy of CeO2 as a promoter in alkaline hydrogen evolution reaction (HER), the underlying mechanism of this effect remains unclear. CoS2, a pyrite‐type alkaline HER electrocatalyst, suffers from sluggish HER kinetics and severe catalyst leaching due to its weak water dissociation kinetics and oxygen‐related corrosion. Herein, it is demonstrated that the interfacial Lewis acid–base Ce∙∙∙S pairs in CeO2 ‐loaded CoS2 effectively improve the catalytic activity and durability. In CeO2 ‐loaded CoS2 nanowire array electrodes, these interfacial Lewis acid–base Ce∙∙∙S pairs with unique electronic and structural configurations efficiently activate water adsorptive dissociation and kinetically accelerate hydrogen evolution, delivering a low overpotential of 36 mV at 10 mA cm −2 in alkaline media. Such Ce∙∙∙S pairs also weaken O2 adsorption on CoS2, leading to undecayed activity over 1000 h. These findings are expected to provide guidance for the design of CeO2 ‐based electrocatalysts as well as other hybrid electrocatalysts for water splitting. Abstract : Interfacial Lewis acid–base Ce∙∙∙S pairs play the crucial role in CeO2 /CoS2 electrocatalysts for efficient and robust alkaline hydrogen evolution production. Such pairs with unique electronic and structural configurations effectively activate water adsorptive dissociation, kinetically accelerating hydrogen evolution, and also weaken O2 adsorption on CoS2, suppressing the catalyst leaching.